2013
DOI: 10.2500/ajra.2013.27.3845
|View full text |Cite
|
Sign up to set email alerts
|

Serum Eosinophil Cationic Protein Level in Chinese Subjects with Nonallergic and Local Allergic Rhinitis and its Relation to the Severity of Disease

Abstract: The present study provides the first evidence that LAR exists in Chinese subjects. This study also suggests that eosinophils and ECP take part in the pathogenesis of NAR. A local examination for ECP and specific IgE in nasal lavage fluid or secretions in patients with LAR should be performed in a future study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
42
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 24 publications
2
42
1
2
Order By: Relevance
“…Only one study has reported the evidence that LAR existed in Chinese subjects [7]. That study showed there was no difference between LAR and NAR patients with regard to the clinical symptoms, which was in contrast to findings in Caucasian patients.…”
contrasting
confidence: 46%
See 2 more Smart Citations
“…Only one study has reported the evidence that LAR existed in Chinese subjects [7]. That study showed there was no difference between LAR and NAR patients with regard to the clinical symptoms, which was in contrast to findings in Caucasian patients.…”
contrasting
confidence: 46%
“…The current studies demonstrated the patterns and phenotypes of LAR patients from mainland China, where there is a dearth of research in LAR, with only 1 existing study in Chinese patients [7]. We found that the proportion (19.0%) of LAR among the IR subjects in our study was lower than the results reported in Western countries (e.g., Spain 54-62.5%) but similar to other Asian countries (e.g., Korea 10.8%) [3,4,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the obtained results, D. pteronyssinus was the predominant allergen that caused AR or LAR in the analyzed groups, a result in agreement with previous data, which showed that D. pteronyssinus may have great importance in the induction of LAR among various age groups [11,12]. The course of nasal symptoms, regardless of severity, in this type of allergy can mimic chronic non-AR; therefore, in a significant group of patients, the true diagnosis of LAR was significantly delayed.…”
Section: Discussionsupporting
confidence: 79%
“…However, eosino-phil derived proteins such as eosinophil derived neurotoxin (EDN) and major basic protein (MBP), and the mean peripheral blood eosinophils (PBE) count have proven to be significantly higher in patients with EoE, both in serum and histological samples (EDN and MBP). Eosinophil cationic protein (ECP) in serum has proven to be effective in the clinical monitoring of asthma and allergic rhinoconjunctivitis (6). However, its role in EoE has not been studied in depth.…”
Section: Introductionmentioning
confidence: 99%